The Effect of Marketing Communication Mix on Customer Purchase Decision (Study on the customers of PT. Semen Indonesia (persero) Tbk) - Dita Kusuma Wardani; Arma nu (Jurnal Ilmiah Mahasiswa FEB, 2014)
Getting customers and strengthening brand in the competition among companies become the basic needs for companies to find the most effective way in market. In the marketing world, almost every company that competes uses a number of media to communicate  its  product and brand through a variety of marketing communication programs.  Problem solving ability of the marketing communication  strategy  is essential for the company. Marketing communication  is  significantly important to achieve a successfulness of a company in the field of marketing through various programs which are aimed to establish a good relationship with the customers. These research shows that there is positive relationship between marketing communication mix  and  customer purchase decision. Marketing communication mix including advertising, sales promotion, direct marketing, and public relation.Keywords:  Advertising, Sales Promotion, Direct Marketing, Public Relation, Customers Purchasing Decision.